Influence of Psychological Distress and Burnout on Quality of Life Among Road Safety Employees in Benue State Sector Command - Zakariah, Danladi; Ihaji, Elvis O.; Anhange, Samuel T. (Darul Yasin Al Sys, 2024)
This study investigated the influence of psychological distress and burnout on quality of life among Road Safety Employees in Benue State Sector Command. The study employed cross sectional and expost facto design where 200 participants consisting of 161 (80.5%) males, 37 (18.5%) females and 2 (1.0%) did not indicate their sex. Their ages ranged from 21-60 years with means age of 35.55 (SD=7.21). Kessler psychological Distress scale (K10), Maslach Burnout Inventory (MBI) and quality of Life Scale (WHOQOL) were used for data collection using Multistage, Stratified random and systematic sampling techniques. Statistical analysis involved the use of multiple regression. Findings indicated that, there was a significant negative influence of psychological distress and burnout on quality of life among Road Safety Employees in Benue State Sector Command. On individual basis, psychological distress had a significant negative on physical health, psychological health and social relationship, except for environmental mastery that proved to be insignificant. Furthermore, there was significant joint influence of burnout on the overall quality of life among Road Safety Employees in Benue State Sector Command. On individual basis, burnout significantly influenced physical health, psychological health, social relationship and environmental mastery. Finally, there was a significant joint influence of psychological distress and burnout on overall quality of life among Road safety employees in Benue State Sector Command. On the dimensions of quality of life, psychological distress and burnout jointly influenced physical health, psychological health, social relationship and environmental mastery dimensions of quality of life significantly. Based on the findings of this study, it was recommended that conscious efforts should be made to enhance quality of life among Road Safety Employees through reduction of psychological distress and burnout inherent among Road Safety Employees in Benue State Sector Command in particular and Nigeria at large.